Perfil fitoquímico, atividades antioxidante e antimicrobiana de amora-preta (Rubus fruticosus) cv. Tupy em diferentes estádios de maturação cultivada em clima temperado - Azevedo, Miriane Lucas (2010)
Blackberry (Rubus fruticosus) is considered a fruit rich in the phytochemical compounds, mainly phenolic acids and anthocyanins, which have a high potential for antioxidant and are also present L-ascorbic acid, carotenoids and tocopherols. Based on the concentration changes that these compounds undergo during the fruit ripening stages, this work aims to study the changes in the phytochemical profile of blackberry cv. Tupy, grown in temperate climates, in Pelotas, and effects on antioxidant and antimicrobial activity. Were determined five stages of ripening from green to mature through the external color of the fruit, and to confirm the differences between them, each stage was measured physical-chemical, determining total acidity (TA), total soluble solids (SS),ripening index (SS/TA) and instrumental analysis of color (hue angle). With regard to the phytochemical profile were analyzed phenolic compounds, L-ascorbic acid, carotenoids and tocopherols. It can be stated that according to the results of the different ripening stages did not affect significantly (p≤0.05) the total phenolic compounds, catechin and L-ascorbic acid. For the individual phenolic compounds during the fruit development, the derivatives of benzoic acid increased, the same behavior occurs with epicatechin, that among these is composed of higher concentration, the levels of cinnamic acid derivatives showed a different behavior, there fall of these levels. Anthocyanins increased during the fruit ripening, detaching the cyanidin-3-glucoside. The carotenoids and tocopherols decreased during ripening. One can conclude that it is possible to mount a phytochemical profile of blackberry cv. Tupy, grown in temperate climates, to differentiate their ripening stages, but it is necessary to carry out several determinations, since it is not possible to say which assessment contributed most to the differentiation of stages along the ripening. Another observation concerns the antioxidant activity increased during ripening, in vitro and in vivo, but noted that it is not possible to determine which compound has a higher antioxidant capacity in isolation, but found that there was a synergism between the phytochemical compounds present in fruit, which vary over the course of its development. Likewise, we can not say if there was an increase in antimicrobial activity over the course of ripening, and even if there was a specific secondary compound responsible for this antimicrobial activity, but that it exists, since the bacterium Salmonella enteritidis showed sensitivity to the extracts but with different answers.